Analysis of the Bioprotective Potential of Different Lactic Acid Bacteria Against Listeria monocytogenes in Cold-Smoked Sea Bass, a New Product Packaged Under Vacuum and Stored at 6 ± 2°C - Iacumin, Lucilla; Cappellari, Giorgia; Pellegrini, Michela; Basso, Marco; Comi, Giuseppe (Frontiers in Microbiology, 2021)
The aim of the work was to monitor the presence of Listeria monocytogenes in cold-smoked fish products (trout, salmon, and sea bass) marketed in Italy. Cold-smoked sea bass is a new product that has not yet been commercialized and was collected from the production facility. Monitoring data have shown that cold-smoked products can be contaminated by L. monocytogenes, the presence of which has been highlighted mainly by enrichment culture (presence in 25 g). The isolated Listeria were serotyped and belonged mainly to low-virulence serotypes (1/2c), followed by serotypes 1/2a, 1/2b, and 4b. Furthermore, considering the ability of L. monocytogenes to grow in these products due to their chemical–physical characteristics (pH > 6.0, Aw > 0.97) and long shelf life at 4°C, an additional aim was to verify the activity of different bioprotective starters, including Lactilactobacillus sakei (LAK-23, Sacco srl, Via Alessandro Manzoni 29/A, 22071 Cadorago, CO, Italy), Carnobacterium spp., Lacticaseibacillus casei (SAL 106), and Lacticaseibacillus paracasei (SAL 211), in cold-smoked sea bass. All starters were bacteriocin producers. For this experiment, smoked sea bass samples were intentionally inoculated with a mixture of three different strains of L. monocytogenes and of each starter culture. After inoculation, the smoked sea bass were vacuum-packed and stored at 6 ± 2°C for 60 days, simulating the typical abuse storage temperature of markets and home refrigerators. At 0, 15, 30, 45, and 60 days, the sea bass samples were analyzed to evaluate the effectiveness of the starters against L. monocytogenes. Listeria monocytogenes growth was prevented only by the addition of the LAK-23 starter. Indeed, at the end of the shelf life, the amount of L. monocytogenes observed was similar to that in the inoculum. Consequently, the use of this starter can allow the inclusion of cold-smoked sea bass or smoked fish products in category 1.3 of Regolamento CE 2073/2005, which are products that do not support the growth of this microorganism. Finally, the activity of the LAK-23 starter did not produce an off flavor or off odor in the smoked sea bass.